2022
DOI: 10.1007/s13300-022-01309-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes on the Recurrence and Prognosis of Acute Kidney Injury in Older Male Patients: A 10-Year Retrospective Cohort Study

Abstract: Introduction: While patients with diabetes are at higher risk of developing acute kidney injury (AKI), there are few studies on the recurrence of AKI in older adult patients. This study therefore aimed to examine the impact of diabetes on AKI recurrence and long-term outcomes in older male patients. Methods: This retrospective cohort study included older male patients who experienced AKI during hospitalization from July 2007 to August 2011. Medical records of all patients were followed up for 10 years. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…There have been 2 retrospective analyses, both of which had conflicting findings. [10,57] Diabetic patients had less severe AKI, recovery to baseline renal function and the proportion of patients developing progressive CKD was lower in the diabetic group as shown by Johns et al [10] However, the 10-year retrospective analysis done by Xin S et al showed that the recurrence rate of AKI was higher in the diabetic group than in the nondiabetic group. [57] Between diabetes and nondiabetic groups, mortality was comparable in both retrospective analyses.…”
Section: Aki In Diabetic Versus Nondiabetic Patientsmentioning
confidence: 99%
“…There have been 2 retrospective analyses, both of which had conflicting findings. [10,57] Diabetic patients had less severe AKI, recovery to baseline renal function and the proportion of patients developing progressive CKD was lower in the diabetic group as shown by Johns et al [10] However, the 10-year retrospective analysis done by Xin S et al showed that the recurrence rate of AKI was higher in the diabetic group than in the nondiabetic group. [57] Between diabetes and nondiabetic groups, mortality was comparable in both retrospective analyses.…”
Section: Aki In Diabetic Versus Nondiabetic Patientsmentioning
confidence: 99%
“…Diabetes is a global public health concern that is associated with high morbidity. [ 1 ] The incidence of diabetes has been rapidly increasing in China, and has the highest prevalence of approximately 12% in people aged 70 to 80 years. [ 2 , 3 ] The pathophysiological changes associated with diabetes in elderly patients include abnormal insulin secretion or defective insulin action, mainly characterized by chronically elevated glucose levels and extended disease duration.…”
Section: Introductionmentioning
confidence: 99%